THE ROLE OF CONTINUOUS TRAINING IN IMPROVING THE COMPETENCE OF PRIMARY SCHOOL TEACHERS: PERSPECTIVES AND CHALLENGES - Wardati Khumairah Rusdi; Amândio de Araújo Sarmento; Rafika Nisa (Adisam Publisher, 2025)
Continuous training plays a crucial role in improving the competence of primary school teachers amidst the rapid development of technology and learning methodologies. This article explores how continuous training not only updates teachers' knowledge and skills but also assists in the implementation of relevant new teaching methods. However, the implementation of this training is faced with challenges such as budget constraints, logistical issues and lack of institutional support. Therefore, innovative strategies and effective collaboration from all parties involved are needed to ensure that the training can run well and effectively. The ultimate goal is to ensure that teachers have the competencies needed to guide students towards a brighter future.